Estes Park Volunteer Fire Department and town of Estes Park - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2005)
Located in: Fort Collins office files. Estes Park Volunteer Fire Department and the Town of Estes Park records related Colorado State Forest Service (CSFS) program for community slash disposal. Includes: Wildland Urban Interface (WUI) grant applications; grant reports and reimbursement requests; cooperative match project and scope of work reports; financial statements and invoices; correspondence; and notes.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado